THE EFFECT OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 13 PEKANBARU IN COMPREHENDING NARRATIVE TEXT - Deani, Amira; Mahdum, Mahdum; Eliwarti, Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is aimed to find out whether or not there is significant effect of Cooperative Integrated Reading and Composition (CIRC) on the Ability of the Second Year Students of SMPN 13 Pekanbaru in Comprehending Narrative Text. The research design is a pre-experimental research with one group pre-test and post-test design. The sample was VIII-7 chosen by using cluster random sampling technique. In order to collect the data, the pre-test and post-test were administered and then the data were statistically analyzed by using the t-test formula. The result showed that the mean score of post-test was higher than mean score of pre-test. The value of t-test was higher than t-table at 5% of the significance level and t-table at 1% of the significance level. Therefore, Alternative Hypothesis (Ha) was accepted and Null Hypothesis (Ho) was rejected. It could be concluded that there was significant effect of Cooperative Integrated Reading and Composition (CIRC) on the Ability of the Second Year Students of SMPN 13 Pekanbaru in Comprehending Narrative Text.Keywords: Cooperative Integrated Reading and Composition (CIRC), Reading Comprehension